PENDAMPINGAN KEMITRAAN UMKM GO DIGITAL BAGI NEW ENTREPRENEUR MAKE-UP ARTIST DI DESA WAY HUI - Niken Kusumawardani; Dewi Sukmasari; Dwiyana Habsary; Susi Sarumpaet (Universitas Teknokrat Indonesia, 2022)
MSMEs go digital is a government program as an effort to save MSMEs during the Covid-19 pandemic. This program is an effort to market MSME products through digital platforms, one of which is through social media. The increase in social media users from year to year plus the pandemic period increasingly encourages a drastic increase, this is what provides opportunities for MSME actors. The Make-Up Artist (MUA) is one of those affected by the social restriction policy during the pandemic, but this business is very promising among millennials and generation Z. For this reason, this service activity is carried out as a means of mentoring and empowering young entrepreneurs pioneering ( new entrepreneur) in achieving optimal promotions digitally, providing convenience, cost efficiency, and being able to reach consumers. Furthermore, this activity also helps new entrepreneurs in determining digital personal branding. The results of this activity are participants' understanding of the promotion of MUA's products and services through social media, personal branding and marketing development through Instagram promotions and also to build a network of groups or associations of young Make-Up Artist entrepreneurs.